Students activities notification system / Nur Khairani Kamarudin, Mohd Faris Mohd Fuzi and Ahmad Haziq Abu Bakar - Kamarudin, Nur Khairani; Mohd Fuzi, Mohd Faris; Abu Bakar, Ahmad Haziq (UiTM Cawangan Perlis, 2017)
Student portal is an official website of UiTM. The function of student portal is to spread the new information or activities for the current semester. The examples of information are date of course registration, date of validation, date of result final exam, faculty or club activities. From my survey, I found that it is hard to get new information. They have to log in into student portal to enable them to get the latest news. To solve this problem, an Android Mobile for Students Activities Notification System was being created using Android platform. This project was developed using hardware and software. The hardware is using mobile phone with Android operating system and personal computer for the server. Android SDK (System Development Kit) was used to develop the Android Mobile for Students Activities Notification System that compatible for Android operating system. These projects were conduct usability test and transmission of update information from server to client. As long as student is connected to the Internet, they can get the notification of new information that is being update. This project involve with server client communication. This project is important because it helps student to get or receive new update information without have to log in into student portal.